Naprężenia Kontaktowe w Procesie Plastycznego Płynięcia Kształtowego Osiowo-Symetrycznego Stempla - L. Dietrich (Engineering Transactions, 1970)
In the paper the method and results are given of the measurements of the normal contact stresses occurring on a frontal surface during compression in the plastic range of an axial-symmetrical stamp in the shape of a truncated cone. Experimental investigations were carried out for two batches of samples differing in the angle of inclination of the generator of the cone, made of lead. The distribution of normal stresses determined on the basis experiments differs essentially from the distribution calculated on the basis of the equation of the theory of plasticity. The graphs plotted on the basis of the performed measurements possess a distinct accumulation of the stresses on the external radius of the frontal surface; the degree of this accumulation is however smaller than it follows from solution of the theory of plasticity.